Neuroprotection in Traumatic Brain Injury: Mesenchymal Stromal Cells can Potentially Overcome Some Limitations of Previous Clinical Trials - Carbonara, Marco; Fossi, Francesca; Zoerle, Tommaso; Ortolano, Fabrizio; Moro, Federico; Pischiutta, Francesca; Zanier, Elisa R.; Stocchetti, Nino (Frontiers in Neurology, 2018)
Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. In the last 30 years several neuroprotective agents, attenuating the downstream molecular and cellular damaging events triggered by TBI, have been extensively studied. Even though many drugs have shown promising results in the pre-clinical stage, all have failed in large clinical trials. Mesenchymal stromal cells (MSCs) may offer a promising new therapeutic intervention, with preclinical data showing protection of the injured brain. We selected three of the critical aspects identified as possible causes of clinical failure: the window of opportunity for drug administration, the double-edged contribution of mechanisms to damage and recovery, and the oft-neglected role of reparative mechanisms. For each aspect, we briefly summarized the limitations of previous trials and the potential advantages of a newer approach using MSCs.